Enhancing mathematical language through oral questioning in primary schools - Mahmud, Muhammad Sofwan (Society for Research and Knowledge Management, 2020)
Fluency in mathematical language is essential in helping students to master mathematics content. This qualitative case study was conducted to describe how mathematics teachers apply mathematical language to students in the oral questioning process. Data were collected through observations, interviews, and field notes. Six mathematics teachers from six different primary schools were selected as participants of the study using a purposive sampling method. The data were then analyzed using a constant comparative method to identify the patterns and themes that emerged from the data obtained.Â The study found that students were questioned by emphasizing the correct pronunciation and were asked mathematical terms and keywords to improve their mathematical language ability through oral questions. To enhance mathematical language, the teacher also restated terms in the teachersâ€™ own words, asking using verbal-cloze questions, asking questions about mathematical terms repeatedly and using seeking-clarification questions. Thus, the use of various approaches in oral questioning had helped students to improve their fluency of mathematical language and enabled them to understand mathematical concepts better.Â Â Therefore, teachers need to understand the role played by oral questioning in the teaching of mathematical language to students.